Vector competence of pre-alpine Culicoides (Diptera: Ceratopogonidae) for bluetongue virus serotypes 1, 4 and 8 - Paslaru, Anca Ioana (Parasit Vectors, 2018)
BACKGROUND: Bluetongue disease, caused by bluetongue virus serotype 8 (BTV-8), appeared for the first time in the northern part of Europe in 2006, and subsequently rapidly spread causing severe economic losses to the farming industry. The implicated vectors of BTV in Europe are Culicoides species within the subgenus Avaritia (C. chiopterus, C. dewulfi, C. obsoletus and C. scoticus). Epidemiological data from Switzerland have shown that BTV, whose spread was eliminated at an early stage by vaccination campaigns, had not been circulating among livestock at higher altitudes where other species dominate the Culicoides fauna. In this study, we investigated the extent that Culicoides spp. prevailing at higher altitudes (mainly C. grisescens) can act as vectors for BTV. METHODS: Culicoides were collected at farms in the pre-alpine region (two sites at 1550 m above sea level, masl, referred to as pre-alpine I; one site at 2030 masl, pre-alpine II) and, for comparative purposes, from the Swiss Plateau (one site, 650 masl). They were fed on bovine blood/BTV suspensions (BTV-1, 4 or 8) and incubated for eight days under a fluctuating temperature regime (13–25 °C, mean 19 °C), reflecting a mid-summer warm spell in the pre-alpine region. Susceptibility to BTV transmission was assessed from head homogenates by RT-qPCR and virus isolation. RESULTS: Overall, 9196 female Culicoides were exposed to the three BTV strains through an artificial membrane, with feeding rates of 14–27%. Survival rates of blood-engorged Culicoides females at eight days post-infection depended on both virus serotype and altitude of origin. Virus dissemination (C(q) ≤ the cut-off value as determined by serial virus dilutions) was confirmed only for BTV-1 in C. scoticus (dissemination efficiency 22.5%; 9/40) and C. obsoletus (5.6%; 1/18) from the Swiss Plateau area. There was no strong evidence of susceptibility to infection for Culicoides from the pre-alpine area when fed with all BTV strains (BTV-1, 4 and 8). CONCLUSIONS: This study confirms the susceptibility of C. scoticus and C. obsoletus to BTV-1 infection, including under cooler temperatures. Culicoides grisescens, which is highly abundant at higher altitudes, cannot be considered a potential vector under these temperature conditions. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13071-018-3050-y) contains supplementary material, which is available to authorized users.